Inhibitory effect of non‐thermal plasma synergistic Tegafur on pancreatic tumor cell line BxPc‐3 proliferation. Issue 3 (3rd January 2019) - Chang, Zhengshi; Li, Guoqiang; Liu, Jinren; Xu, Dehui; Shi, Xingmin; Zhang, Guanjun
Abstract : In this paper, a glow‐like helium atmospheric pressure plasma jet is combined with clinical antitumor drug‐Tegafur‐ to treat pancreatic tumor cells in vitro. The results reveal that they have a synergistic effect on inhibiting the proliferation of tumor cells when the plasma is applied before the drug, but the antagonism between drug and plasma meets in the other case. The results are hopeful to promote the application of the plasma combining the drugs in clinic therapy for cancer. Abstract : In this paper, a helium atmospheric pressure plasma jet is combined with clinic antitumor drug Tegafur to treat pancreatic tumor cells in vitro. The results reveal that they have a synergistic effect on inhibiting the proliferation of tumor cells when the plasma is applied before the drug, but in some cases may be counterproductive. The results indicate the potential of a combination of plasma and traditional methods in clinic therapy for cancer.